Investment, Funding Decisions, Firm Value with Corporate Governance as Variable Moderation in Indonesia Stock Exchange - Djuminah Djuminah; Rahmawati Rahmawati; Ari Kuncara Widagdo; Sri Hartoko; Setianingtyas Honggowati; Siti Nurlaela; Kiswanto Kiswanto (Universitas Negeri Semarang, 2023)
Purpose : This study aims to examine the effect of investment decisions and funding decisions on company value with good corporate governance as a moderating variable in mining companies listed on the Indonesia Stock Exchange and included in the CGPI rating for the period 2017 -2021. The sampling technique was used for 5 years. Method : The sample for this research was purposive sampling with a total sample of 17 state-owned and non-state-owned mining companies. Analysis technique research model using Moderated Regression Analysis (MRA). Findings : The research results show that investment decisions affect firm value. Investment decisions moderated by corporate governance have a positive effect on firm value, while funding decisions moderated by corporate governance have a negative effect on firm value. Novelty: The presence of corporate governance as a moderating variable on the influence of investment decisions and funding decisions on firm value Keywords: Investment Decisions; Funding; Firm Value; Corporate Governance